AUTOMATIC CLUSTERING OF TEXT DOCUMENTS BASED ON A GENETIC ALGORITHM WITH ARTIFICIAL SELECTION - Bodyansky, E. V.; Volkova, V. V.; Koval, K. V. (Radio Electronics, Computer Science, Control, 2024)
The new genetic algorithm with artificial selection is proposed. The algorithm is based on the synthesis of ordinary evolutional genetic approach with the ideas of sequential complex-method for extremum searching arbitrary multivariable functions. The algorithm is used for a clusterization of large data collection in a data-processing mode.